Ethnomathematics panting music exploration - Winda Agustina; Rahmita Yuliana Gazali; Zahra Chairani; Maisea Ledua Nareki (Psychology, Evaluation, and Technology in Educational Research, 2021)
There are many interesting things to explore about Panting music related to mathematics. This link between culture and mathematics is known as ethnomathematics. This study aims to determine the mathematical concepts that exist in the Panting and Babun (baboon) instruments. This study uses a descriptive method with qualitative data that involved South Kalimantan cultural and Panting musicians in Banjarmasin, a lecturer in the art and culture of music subject at STKIP PGRI Banjarmasin, and students of the Dance Education study program at STKIP PGRI Banjarmasin. Data collection techniques through interviews, observations, and online questionnaires. The data obtained were reduced and presented descriptively—data triangulation using collection techniques and sources. The results of this study indicate (1) mathematical concepts on the Panting instrument are measurement, circle, multiples of 5, the position of two lines that coincide, and the position of lines that are equidistant, and (2) mathematical concepts on the Babun instrument are truncated cones, odd numbers, circle, the position of equidistant lines, isosceles triangle, rhombus, and congruence of plane figures.